Impact of IGFBP-3 A-202C genetic variant on breast cancer susceptibility and serum biomarkers (IGFBP-3 and IGF-1) in Palestinian women. - Heba Mohammed Arafat; Tengku Ahmad Damitri Al-Astani; Noorazliyana Shafii; Rosediani Muhamad; Ohood Mohammed Shamallakh; Ihab Naser; Nahed Al Laham; Alaa Siddig (PLoS ONE)
Breast cancer is the most common diagnosed cancer and the leading cause of cancer-related deaths among women globally. This study examined the impact of insulin-like growth factor binding protein-3 (IGFBP-3) A-202C polymorphism (rs2854744) on breast cancer risk and its association with insulin-like growth factor-1 (IGF-1) and IGFBP-3 serum levels among Palestinian women in the Gaza Strip. Understanding these genetic variants could guide the development of early detection strategies and personalized interventions for breast cancer in underrepresented populations. A case-control study involved 112 women with newly diagnosed breast cancer and 222 healthy controls. Genotyping of the IGFBP-3 A-202C polymorphism was performed using polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP), and serum IGFBP-3 and IGF-1 levels were measured. The CC genotype of IGFBP-3 A-202C was observed in 70.5% of cases and 20.7% of controls, conferring a 16-fold increased breast cancer risk (OR=16.237; 95%CI 7.904, 33.356, p ≤ 0.001). The AC genotype was found in 19.6% of cases and 32.4% of controls, also associated with ~ 3-fold increased risk (OR=2.889; 95%CI 1.319, 6.325, p = 0.008). The CC genotype conferred a 28-fold increased risk in premenopausal women (OR=28.050; 95%CI 10.281, 76.527, p ≤ 0.001) and 5-fold in postmenopausal women (OR=5.333; 95%CI 1.711, 16.620, p = 0.004). Women with the CC genotype had the highest mean serum IGF-1 levels (116.49 ng/mL, p ≤ 0.001) and IGFBP-3 levels (3.76 µg/mL, p = 0.006) compared to those with the AA genotype. Positive correlations were observed between IGFBP-3 polymorphism and serum IGF-1 (rs = 0.175, p ≤ 0.001) and IGFBP-3 levels (rs = 0.164, p = 0.003). The IGFBP-3 A-202C polymorphism, especially the CC genotype, is strongly associated with elevated serum IGFBP-3 and IGF-1 levels and increased breast cancer risk, highlighting its potential as a biomarker for breast cancer screening and risk stratification. Further studies are needed to validate these findings in diverse populations.